Implementación de inteligencia de negocios con Power BI en el Z-Market de la Escuela Agrícola Panamericana Zamorano - Lazo, Carlos E.; Ortiz G., Mauricio H. (Zamorano: Escuela Agrícola Panamericana, 2023)
Business intelligence programs represent highly beneficial tools that facilitate the work of managers by allowing them to effectively interpret sales behaviors and compliance with other indicators. The adoption of Power BI will prove to be a highly efficient solution, providing decision-makers with not only a more agile process but also a more accurate one. A meeting was held to clarify the operations performed by Z-Market, which helped identify its challenges and the important data to be projected on the interactive Dashboard. Giving way to the receipt of data to start the ETL process (extraction, transformation, and loading of data), a process that is done to load the data to the Power Bi (Power Business Intelligence) tool. The main distinguishing feature of Power BI lies in its ability to handle large volumes of data, which could be verified with data granted from 2018 to July 2023. Followed by the development of the interactive Dashboard, where it was possible to accurately visualize the best-selling products in each internal production plant and make exhaustive sales comparisons between different months, quarters, and years. In addition, we obtained a detailed average of target achievement and the ability to formulate queries through natural language to generate instant and highly informative graphics. It was concluded that the implementation of this tool has proven to be highly effective in avoiding the stagnation of "old" methods and fostering innovation. Not only by simply interpreting behaviors, but also by identifying market trends that will drive sales and, consequently, generate significant growth in profits.